Metabolomics profiling of strawberry (Fragaria x ananassa) F1 population to characterize flavour and nutritional traits - Pott, Delphine; Medina, Juan Jesús; Fernie, Alisdair R; Amaya Saavedra, Iraida; Vallarino Castro, José G.; Osorio-Algar, Sonia (My University, 2018)
The cultivated strawberry (Fragaria x ananassa) is a highly consumed fruit known for its delicate flavour and nutritional characteristics. However, as fruit quality attributes have been lost after years of traditional breeding, new technological tools, such as high throughput metabolomics, are necessary for the identification of factors responsible of these traits. Here we present the metabolomics profiling for the content of primary and secondary metabolites of a 95 F1 individuals strawberry population derived from genotype “1392”, selected for its superior flavour, and “232” (Zorrilla-Fontanesi et al., 2011; Zorrilla-Fontanesi et al., 2012). Metabolite profiling was performed on mature fruits of the strawberry population using gas chromatography hyphenated to time-of-flight mass spectrometry for primary metabolites and ultra performance liquid chromatography Exactive Orbitrap tandem mass spectrometry for secondary metabolites.
Keywords: Metabolitos - Congresos; Metabolomics; strawberry; QTL